2011
DOI: 10.1097/iae.0b013e31820a6850
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Laser Ophthalmoscope Imaging Stabilized Microperimetry in Dry Age-Related Macular Degeneration

Abstract: Scanning laser ophthalmoscope microperimetry is able to detect changes in retinal sensitivity in AMD patients overlying drusen and at the margin of GA. It is a useful device to grade focal retinal sensitivity in patients with dry age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
53
4
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 30 publications
7
53
4
4
Order By: Relevance
“…[8][9][10][11] In contrast, other studies reported no difference in sensitivity between drusen and nondrusen areas.…”
mentioning
confidence: 41%
“…[8][9][10][11] In contrast, other studies reported no difference in sensitivity between drusen and nondrusen areas.…”
mentioning
confidence: 41%
“…Previous studies of microperimetry in AMD have included patients with dry AMD, 13,14 and patients with nvAMD that have been treated with verteporfin photodynamic therapy, 9 autologous RPE-choroid graft, 15 360 degree macular translocation, 16 systemic bevacizumab, 17 intravitreal bevacizumab, 8 and intravitreal ranibuzumab. [18][19][20] Bolz et al 18 conducted a prospective study to evaluate the functional and morphological effects of three loading doses of intravitreal ranibizumab in 29 patients (29 eyes) with previously untreated nvAMD.…”
Section: Discussionmentioning
confidence: 99%
“…First, the inner 3,4 , outer 5 and total 6 retinal thicknesses change. Second, drusen (extracellular deposits) occur between the retinal pigment epithelium (RPE) and Bruch's membrane 7,8 . As such, both drusen volumes and thicknesses of various retinal layers are of interest as potential biomarkers for disease monitoring and diagnosis.…”
Section: Introductionmentioning
confidence: 99%